1994
DOI: 10.1063/1.357590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conjugated bonds on the charging of insulating polymers

Abstract: Different densities of conjugated bonds, which affect the polarization states necessary in forming polarons, are generated by stretching polymers at various rates. An investigation of the charging of the stretched high-impact polystyrene and high-density polyethylene by using a scanning electron microscope technique is made. The experimental results reveal that polymer charging is related to electron trapping as polarons at the polarized sites of the polymeric chains, confirming the recent interpretation of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Electron trapping, leading to the formation of space charges in insulators such as ceramics, 1-6 glasses, 2 and polymers [7][8][9][10][11][12] under nonpenetrating electron beam irradiation, has been observed for a long time and has attracted much interest because it is strongly related to the properties of a material such as complex permittivities ͑⑀Ј,⑀Љ͒, defects, and mobility. 4,5,9,13,14 The study of this phenomenon is an important means of understanding the dielectric strength and flashover phenomenon of insulators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron trapping, leading to the formation of space charges in insulators such as ceramics, 1-6 glasses, 2 and polymers [7][8][9][10][11][12] under nonpenetrating electron beam irradiation, has been observed for a long time and has attracted much interest because it is strongly related to the properties of a material such as complex permittivities ͑⑀Ј,⑀Љ͒, defects, and mobility. 4,5,9,13,14 The study of this phenomenon is an important means of understanding the dielectric strength and flashover phenomenon of insulators.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,9,13,14 The study of this phenomenon is an important means of understanding the dielectric strength and flashover phenomenon of insulators.…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to the breakage of the chains in the amorphous phase (Fig. 8 c) and the formation of conjugated double bonds [12]. The present authors [12] have recently investigated the effect of conjugated bonds on charging and found that the formation of conjugated bonds leads to a decrease in the charging response of a polymer.…”
Section: Discussionmentioning
confidence: 95%
“…It should be noted that the polaron model has been employed also in the interpretation of another phenomenon, charge transport in molecularly doped polymers [7]. Despite the previous explanation of charging in polymers using the polaron concept [12], further confirmation and a more detailed description of the polaron concept in charge trapping is needed. One of our aims is to see whether the polaron concept can be employed in the interpretation of the charging behavior of deformed polymers.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation